Determinación de la densidad óptima de cria postlarval de Myleus schomburgkii (Jardine, 1841) “palometa banda negra” en el IIAP Loreto - Wong Bardales, Deykie Max (2019)
For the research work, it was developed at the Fernando Alcántara Bocanegra Research Center (CIFAB) of the Water and Its Resources Use Research Program (AQUAREC) at the Institute of Amazonian Research of Peru (IIAP), with the main objective of determining the optimal density for postlarval rearing of Myleus schomburgkii “blackbanded palometa” for a period of 15 days. A total of 1,350 postlarvae were used, which came from the Nanay River. The average weights ranged from 0.02 g to 0.03 g, and the length ranged from 1.12 cm to 1.25 cm. These were selected homogeneously and were randomly distributed into 9 tanks of 36 liters capacity, with a useful volume of 15 liters, at densities of T1: 5, T2: 10, and T3: 15 postlarvae/liter of water. They were fed “ad libitum” with a balanced feed containing 50% crude protein, which was ground and sieved. The feedings occurred at different intervals (8, 10, 12, 14, 16, 18, 20, and 24 hours) over the 15-day research period. Weight and length monitoring were conducted at the beginning (day 1), on day 8, and at the end of the experiment (day 15), while parameters such as temperature, dissolved oxygen, pH, nitrites, ammonia, and CO2 levels in the water were recorded daily. Descriptive and inferential statistics were used to analyze the optimal postlarval density treatments. A one-way analysis of variance (ANOVA) was also performed to assess the potential effects of three postlarval rearing densities on various variables, and the results showed no significant differences among the treatments. In fact, the highest weight and length gain was observed in T1 with 0.12 g and 1.92 cm. Survival at the end of the experiment showed a significant difference, with the highest survival rate in T1 at 88% and the lowest in T3 at 33%. Water quality remained within the optimal range: Temperature 27.4°C, pH 7.4, Dissolved Oxygen 4.5 mg/l, Ammonia 0.21 mg/l, CO2 3.5 mg/l.